Azathioprine in inflammatory bowel disease, a safe alternative?. Issue 3 (1998) - Tanis, A. A.
Abstract : Azathioprine and its metabolite 6-mercaptopurine are effective in the treatment of inflammatory bowel disease. They are mostly used for reduction of the use of steroids, maintenance therapy after remission induction by cyclosporin and treatment of fistulae in Crohn's disease. Adverse effects occur in about 15% of patients. The main side effects are pancreatitis, allergic reactions, fever and bone marrow suppression. Symptoms, management and prevention are discussed. A blood monitoring schedule is suggested. Azathioprine and 6-mercaptopurine seem to be safe in pregnancy. There may be a slight increased risk for developing a non-Hodgkin's lymphoma.